2020
DOI: 10.9779/pauefd.532849
|View full text |Cite
|
Sign up to set email alerts
|

Matematiksel Doyum Ölçeğinin (MDÖ) Geliştirilmesi: Geçerlik ve Güvenirlik Çalışması

Abstract: Bu çalışmanın amacı öğrencilerin matematiksel doyum düzeylerini belirlemeye yönelik geçerli ve güvenirli bir ölçme aracı geliştirmektir. Araştırma 2018-2019 eğitim-öğretim yılında toplam 763 öğrenciden oluşan üç ayrı çalışma grubu ile yapılmıştır. Ölçeğin kapsam ve görünüş geçerliği için uzman görüşü alınmıştır. Yapı geçerliği için Açımlayıcı Faktör Analizi (AFA) ve Doğrulayıcı Faktör Analizi (DFA) uygulanmıştır. AFA sonucunda toplam varyansın %59.10'unu açıklayan 19 madde ve üç faktörden oluşan bir yapı elde … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…The total fatalism tendency score is formed by the sum of the scores obtained from all sub-dimensions. As the score increases, the fatalism tendency also increases (16). In our study, the Cronbach Alpha value was found 0.83.…”
Section: Fatalism Tendency Scale (Fts)supporting
confidence: 53%
“…The total fatalism tendency score is formed by the sum of the scores obtained from all sub-dimensions. As the score increases, the fatalism tendency also increases (16). In our study, the Cronbach Alpha value was found 0.83.…”
Section: Fatalism Tendency Scale (Fts)supporting
confidence: 53%
“…It consists of 57 items. Fatalistic tendencies: It was developed by Kaya & Bozkur [ 65 ]. The scale consists of four sub-dimensions, namely Predetermination, Personal Control, Superstition and Luck, and 24 items in total.…”
Section: Methodsmentioning
confidence: 99%
“…Kaya (26) developed the online game addiction scale to assess the consequences of adolescents' online gaming activities. The 5-point Likert-type scale (1=Strongly Disagree and 5=Strongly Agree) is divided into three sub-dimensions.…”
Section: Online Game Addiction Scale (Ogas)mentioning
confidence: 99%
“…The Cronbach's Alpha internal consistency coefficient of the OGAS was 0.91, the internal consistency coefficient of Disruptions was 0.90, the internal consistency coefficient of achievement was 0.88 and the internal consistency coefficient of Economic Gain was 0.83. As a validity study of the scale, the Explanatory Factor Analysis result showed that it represented 58.55% of the total variance and 21 items were grouped under three factors (26).…”
Section: Online Game Addiction Scale (Ogas)mentioning
confidence: 99%